Hormonalny i metaboliczny status we krwi bokserów po 3-rundowej walce - Obminski, Z.; Hübner-Wozniak, E.; Lakomiec, S. (Polish Journal of Sport and Tourism, 2009)
Boxing is one of the combat sports in which the effects of numerous head injuries suffered in competitions may cause neurological disorders, growth hormone deficiency and inhibit the hormonal activity of the pituitary gland. As indicated in papers published by a number of authors, the longer the sports career and/or the greater number of boxing matches, the greater this risk becomes. Hormonal disorders in boxers and kickboxers were detected in the clinical tests involving pharmacological stimulation of the pituitary gland. To date the literature provided no descriptions of either hormonal or metabolic reactions in boxers to intense physical effort which stimulates the hormonal systems. The objective of the study was to determine the post-effort blood status of growth hormone (HGH), cortisol (C), testosterone (T) and lactate (LA) in amateur boxers who participated in the Feliks Stamm International Boxing Tournament, immediately after a 3-round boxing match, in relation to their age and total life-time number of boxing matches. The results showed a very high average HGH level, and furthermore within an astonishingly wide range (8.0 - 132.0 ng/ml). The HGH level showed no correlation with the relative intensity of physical effort which was measured as the level of lactate (4.9 - 20.1 mmol/L), however it was contingent on the anabolic-catabolic ratio (r = -0.528*, p < 0.05). The average C and LA levels were slightly higher, and the T level slightly lower in the case of the defeated contestants (n = 4) than that of the winners (n = 11). No correlation was found between the age, the life-time number of boxing matches and the tested blood parameters in the boxers. The results of hormonal tests give no reason to suspect dysfunction of the pituitary gland and renal cortex. The considerably low T levels in the two contestants (3.0 and 4.2 nmol/L) are difficult to explain without any information gathered in neutral conditions.